The use of Interleukin -10 as a biomarker for diagnosis of viral hepatitis type C Infections and related liver function in beta-thalassemic major patients - Sarah M. Mahmoud; Zainb SE. Abass; Nihad Abdulhussain Jafar (Journal of Madenat Alelem University College, 2018)
Introduction; IL-10 is an important cytokine in the pathogenesis of both infectious and inflammatory processes. The central and necessary role of IL- 10 in protecting against severe or inflammatory pathology has been clearly shown in models of experimental infection with intracellular pathogens using IL-10 genetically deficient mice. IL-10 is a multifunctional cytokine with potent immunoregulatory and anti-inflammatory properties. It prevents the release and function of a number of proinflammatory cytokines. It has been postulated that inadequate levels of IL-10 can determine long-term escape of pathogens from immune control and give rise to persistent infections. The aim of the study is to use of Interleukin -10 as a biomarker for diagnosis of viral hepatitis type C Infections and its relation to liver enzymes in thalassemia patients with viral hepatitis .Patients and methods: A cross sectional study was done on thalassemia patients in gastrointestinal center – Medical city directory in Baghdad from the beginning of March to the end of August 2017. A total of 80 subjects were participated in the present study, (45 thalassemia patients without hepatitis and 35 patients with Thalassemia who receive regular blood transfusion and diagnosed having viral hepatitis type C and were participated in the study. liver enzymes, and IL-10. Alanine transaminase (ALT), and aspartate transaminase (AST) were measured according to standard procedures. Result; there is significant increase in the concentration of IL-10 in the serum of HCV positive patients as compare with control patients. Also, there were significant increase in serum liver enzymes (ALT and AST and ALP), in patients with positive HCV, as compare to control with those with non-viral thalassemia hepatitis.